Plasma heme pool compartmentalization is linked to pathophysiology in Sickle Cell Disease - Moritz Saxenhofer; Daniel Couto; Sandra Mena Perez; Marlies Illi; Justine Brodard; Linet Njue; Ioannis Chanias; Cesare Medri; Gerasimos Tsilimidos; Nicole Hadorn; Christelle Chirlias; Ana-Patricia Batista Mesquita; et al. (PLoS ONE, 2026)
Heme toxicity plays a central role in the pathophysiology of Sickle Cell Disease (SCD), contributing to severe complications such as vaso-occlusion and acute chest syndrome. The continuous release of hemoglobin and heme from increased intravascular hemolysis can exceed the capacity of protective scavenger proteins, leading to heme accumulation in plasma. Interactions with various binding partners result in the formation of different plasma heme species and the compartmentalization of the plasma heme pool. In an observational biomarker study, we used novel bioanalytical assays to quantify plasma heme species in 36 stable-state SCD patients and 36 age, sex, and ethnicity-matched controls. Our results revealed substantially different compartmentalization of plasma heme, despite similar levels of total plasma heme in SCD patients (50 µmol/L) and controls (43 µmol/L). Using a correlation analysis across 85 biomarkers, we examined the association of specific heme species with SCD pathophysiology. Hemopexin-accessible heme (HAH) emerged as a refined indicator of heme burden linked to pathways driving severe SCD complications. A strong inverse correlation was observed between HAH and hemopexin (R = –0.73, p < 0.001), suggesting that hemopexin deficiency contributes to elevated HAH levels. Accurate characterization of clinically relevant plasma heme species and understanding their effects on SCD pathophysiology is essential for the development of new targeted therapies.